The Starr County Border Health Initiative: Focus Groups on Diabetes Prevention in Mexican Americans. Issue 3 (June 2018) - Brown, Sharon A.; Perkison, William B.; García, Alexandra A.; Cuevas, Heather E.; Velasquez, Mary M.; Winter, Mary A.; Hanis, Craig L.
Purpose: The purpose of the study was to conduct focus groups with Mexican Americans in an impoverished rural community on the Texas-Mexico border to identify current barriers to adopting healthier lifestyles and to obtain recommendations for diabetes prevention. Methods: Three separate 2-hour focus groups were led by an experienced bilingual Mexican American moderator. Interviews included questions about cultural factors and barriers that influence lifestyle behaviors, aspects of previous diabetes self-management interventions that were helpful for motivating behavioral change, and recommendations for diabetes prevention. Results: Twenty-seven participants attended a focus group session; each session involved 7 to 12 informants. Individuals were diagnosed with prediabetes or type 2 diabetes mellitus; most were female, foreign born, and Spanish speaking. Interviews documented the cultural importance of food. Informants raised priority issues for diabetes prevention, including the need to learn how to prepare healthier foods and track caloric intake. Major barriers to healthier lifestyles included high costs of healthy foods, fatigue from busy schedules and working multiple jobs, a cultural view that exercise is a waste of valuable time, and fear of deportation. Conclusions: Cultural influences and barriers to implementing healthy lifestyles should be assessed regularly and strategies implemented to overcome them. Such factors may change as environmental, sociocultural, and political environments change.